2012
DOI: 10.1111/j.1365-2966.2012.21090.x
|View full text |Cite
|
Sign up to set email alerts
|

Further investigation of white dwarfs in the open clusters NGC 2287 and NGC 3532

Abstract: We report the results of a CCD imaging survey, complemented by astrometric and spectroscopic follow‐up studies, that aims to probe the fate of heavy‐weight intermediate‐mass stars by unearthing new, faint, white dwarf members of the rich, nearby, intermediate‐age open clusters NGC 3532 and NGC 2287. We identify a total of four white dwarfs with distances, proper motions and cooling times which can be reconciled with membership of these populations. We find that WD J0643−203 in NGC 2287, with an estimated mass … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 84 publications
(140 reference statements)
2
49
0
Order By: Relevance
“…This is the only cluster in our list with known white dwarf members (seven; Reimers & Koester 1989;Koester & Reimers 1993;Dobbie et al 2009Dobbie et al , 2012. In the most recent photometric study of the cluster, Clem et al (2011) confirmed a distance of 492 ± 12 pc and an age of 300 ± 100 Myr.…”
Section: Ngc 3532mentioning
confidence: 80%
See 4 more Smart Citations
“…This is the only cluster in our list with known white dwarf members (seven; Reimers & Koester 1989;Koester & Reimers 1993;Dobbie et al 2009Dobbie et al , 2012. In the most recent photometric study of the cluster, Clem et al (2011) confirmed a distance of 492 ± 12 pc and an age of 300 ± 100 Myr.…”
Section: Ngc 3532mentioning
confidence: 80%
“…Table 1). Red squares mark the positions of the white dwarf candidates, blue circles show the confirmed white dwarfs in NGC 3532 (Dobbie et al 2012). …”
Section: Ruprecht 131mentioning
confidence: 99%
See 3 more Smart Citations